"Behavioural and metabolic risk factors of cardiovascular diseases among post-menopausal women: A cross-sectional study in Itahari sub-metropolitan city of Nepal". - Suraksha Khatri; Deepak Kumar Yadav; Anup Ghimire; Dharanidhar Baral; Birendra Kumar Yadav; Paras Kumar Pokharel (PLoS ONE)
Background and objectives Cardiovascular diseases (CVDs) are main cause of mortality and morbidity among women globally. Menopause, aging and different factors in collaboration leads to increased risk for CVDs among postmenopausal women but study on risk factors of CVDs among postmenopausal women is limited in Nepal. Therefore, we aimed to assess prevalence of behavioural and metabolic risk factors of cardiovascular disease among post-menopausal women. Materials & methods Community based cross-sectional study was carried among 390 post-menopausal women of the Itahari sub-metropolitan city. Multistage simple random sampling technique was used to collect data. Modified semi structured questionnaire STEP I, STEP II and STEP III was used as data collection tool. SPSS version 11.5 used for data analysis. Chi-square test and logistic regressions were performed at 95% confidence interval to find predictors of raised blood pressure and overweight/obesity. Results The mean age of respondents was 63.37 years. The prevalence of current smokers, current alcohol use, less than 5 servings of fruits and vegetables per day, low level of physical activity, overweight/obesity and raised blood pressure was 9.2%, 18.2%, 86.4%, 52.3%, 56.2% and 44.4% respectively. On multivariate analysis strong predictors of overweight obesity were age ≤59 years (AOR: 3.21, CI 1.49-6.89), poor economic status (AOR: 1.764, CI: 1.120-2.779) and low physical activity (AOR: 2.132, CI: 1.350-3.370). Predictors of raised blood pressure were age ≥75 years (AOR: 2.04, CI: 1.01-4.11), unmarried and widow (AOR: 1.815, CI: 1.108-2.971), higher economic status (AOR: 1.752, CI: 1.119-2.740) and smoking (AOR: 4.109, CI: 1.737-9.718). Conclusion Prevalence of behavioural and metabolic risk factors among postmenopausal women in Itahari sub-metropolitan city were alarmingly high. This calls for an early need of intervention and policies at local, provincial and institutional level to address risk factors of CVDs.